Esthetic enhancement of a traumatized anterior tooth with a combination of forced eruption and tooth alignment: a case report - So-Hee Kang; Myoung-Uk Jin; Sung-Kyo Kim; Young-Kyung Kim (Korean Academy of Conservative Dentistry, 2016)
Exposing sound structure of a subgingivally fractured tooth using orthodontic extrusion is considered to be a conservative way to re-establish biologic width without sacrificing esthetics or jeopardizing periodontal support of neighboring teeth. When a misaligned tooth is traumatically involved, a more comprehensive approach combining tooth extrusion and re-alignment may be necessary for a successful restorative outcome. This case report describes a successful esthetic management of a patient with complicated crown-root fracture on the maxillary right central incisor and pre-existing malocclusion in the maxillary anterior region. Forced eruption along with re-alignment of teeth by orthodontic movement seems to allow re-positioning of the fracture line to a favorable position and correction of crowding, providing a better esthetic result.